Pemaknaan Sufisme: Analisis Isi Instagram Habib Husein Ja’far Al Hadar - Pane, Sarmalina; Sahrin, Abu (Lembaga Yasin AlSys, 2023)
The influence of the internet and social media on the study of the younger generation of Sufism cannot be separated from these elements. Sufism can now be expressed in a virtual space that is more symbolic because it only gives birth to Sufi forms. Sufism messages conveyed on social media in a fresh and modern way inevitably influence religion that adheres to modernity. Habib Husein Ja'far is one of the preachers who makes the topic of Sufism the focus of his sermon. Habib Husein Jafar is a content developer who always preaches through social media while also practicing Islam of Love. Researchers in this study looked at Habib Husein Ja'far's Instagram posts about Sufism and his interpretation of Sufism. This investigation was carried out in the library. Digital ethnography is the research methodology used. content analysis or content analysis will be used to answer the problems identified in the problem formulation. The results that the researchers found were that there were 270 posts with the issue of Sufism uploaded by Habib Husein Ja'far's Instagram account from 7 March 2018 to 20 August 2023. In Habib Husein Ja'far's view, the essence of Islam is Sufism itself. The pillars of Ihsan teach about Sufism, namely about worshiping God as if God sees us. Sufism is the pinnacle of Islam, because after we become Muslims (practice Islamic teachings) and have faith (practice Islamic religious teachings with full faith, not just practice). So humans need to reach the top of the climb, namely ihsan.